USING HORIZONTAL SUBSURFACE FLOW CONSTRUCTED WETLAND SYSTEM IN THE TREATMENT OF MUNICIPAL WASTEWATER FOR AGRICULTURE PURPOSES - & Faisal, Rahi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Reuse of treated wastewater for irrigation purpose can reduce high pressure on freshwater resources. A horizontal subsurface flow constructed wetland (HSSF CW) system filled with gravel and planted with Phragmites Australia was used to treat the real wastewater at Al-Rustumia wastewater treatment plant. Some characteristics of wastewater such as biochemical oxygen demand, phosphate and total suspended solids have been monitored from 15 January until 8 July 2018. The results proved that HSSF unit has a good efficacy in the reduction of previous parameters with removal of 84.2, 55.4 and 72.7% while sulphate and total dissolved solids were less removal efficiency with 3.3 and 0.99 % respectively. The measured values of these parameters were within the permissible limits suitable for irrigation purposes.